2006
DOI: 10.1186/1471-2458-6-187
|View full text |Cite
|
Sign up to set email alerts
|

Stages of development and injury patterns in the early years: a population-based analysis

Abstract: Background: In Canada, there are many formal public health programs under development that aim to prevent injuries in the early years (e.g. 0-6). There are paradoxically no population-based studies that have examined patterns of injury by developmental stage among these young children. This represents a gap in the Canadian biomedical literature. The current population-based analysis explores external causes and consequences of injuries experienced by young children who present to the emergency department for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
70
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 30 publications
(50 reference statements)
20
70
2
1
Order By: Relevance
“…The study findings regarding the age at which children are at the greatest risk of each type of poisoning are consistent with previous studies, 8,9,13 and are possibly explained by the development of dexterity, 10 mobility, exploratory, and mouthing behaviour. 7,9,23 Child development, however, cannot explain age differentials between medicinal and non-medicinal products.…”
Section: Comparison With Existing Literaturesupporting
confidence: 80%
“…The study findings regarding the age at which children are at the greatest risk of each type of poisoning are consistent with previous studies, 8,9,13 and are possibly explained by the development of dexterity, 10 mobility, exploratory, and mouthing behaviour. 7,9,23 Child development, however, cannot explain age differentials between medicinal and non-medicinal products.…”
Section: Comparison With Existing Literaturesupporting
confidence: 80%
“…Information on place of occurrence was available for inpatient data only and where place of injury was specified, 83% occurred in the home. This trend is consistent with AIHW statistics (Harris & Pointer, 2012) and international research (Flavin et al, 2006;Gulliver et al, 2005;Phelan et al, 2005). The study findings relate to injuries serious enough to require hospital treatment and did not include minor injuries treated by general practitioners or family and friends.…”
supporting
confidence: 87%
“…Within Australia, as well as in other developing countries, the majority of injuries to children under five years of age occur in the home or neighbouring environment (Flavin, Dostaler, Simpson, Brison, & Pickett, 2006;Gulliver, Dow, & Simpson, 2005;Harris & Pointer, 2012;Phelan, Khoury, Kalkwarf, & Lanphear, 2005). A recent Australian Institute of Health and Welfare (AIHW) report on hospitalised injury in New South Wales found that 89% of children under 1 year and 78% of children 1-4 years were injured in the home (Harris & Pointer, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…[16] As shown in our study, childhood scalding injury is frequently observed among the preschool period, especially between the ages of 2 and 3 years [1][2][3][5][6][7][17][18][19] in which the abilities that increased tendency to injuries were gained such as independent mobility, exploratory behavior, and hand-to-mouth activity. [20,21] Similar to the previous studies from Turkey [23,25] the mechanism of hot milk burns was most commonly the immersion and most frequently affected anatomical parts were the lower extremities and the trunk. Male predominance was demonstrated in our study that in agreement with the previous studies, which had a male to female ratio ranged between 0.9:1 and 2:1.…”
Section: Number Of Patients Mean Burned Bsa (%) Mortality Rate (%)supporting
confidence: 73%